Correction de quelques erreurs dans les editions scientifiques de "L’Histoire hiéroglyphique" (1705) par Dimitrie Cantemir. L’edition Panaitescu-Verdeş (1965) - ȘUTEU, Ștefan (Studia Universitatis Babeș-Bolyai Historia, 2021)
Correction of some errors in the scientific editions of The Hieroglyphic History (1705) by Dimitrie Cantemir. The Panaitescu-Verdeş edition (1965). The Hieroglyphic History, written by Dimitrie Cantemir in 1705, is considered the first Romanian (historical) novel. Beyond the veil of allegory, the exotic topos and animal-related fantasy, the historical events between 1685-1705 are revealed through characteristic deciphering, which can represent valuable data for a historian. The work, first published in 1883, then in 1927 and 1957 in a few non-scientific editions, was finally republished in 1965 in a scientific edition elaborated by P.P. Panaitescu and Ion Verdeş. This particular 1965 edition is of very high historical value, but it also has a number of lacunae, especially in the field of theology. The editors don't reference certain biblical quotes, they hint at certain psychological ideas when mentioning quotes that are clearly extracted from the Bible, they ignore the biblical source, which was the very foundation of Cantemir's maxims, they overlook the study of certain toponyms with biblical origins (Euphrates, Tarshish, Babylon etc.) and don't realize that some of his ideas are of biblical origin (for example: the cyclical evolution of things, free will). Furthermore, they don't distinguish certain elements of Christian iconography from their biblical counterparts, leading to confusion (according to the editors, Saint Veronica's Veil is attributed to Magdalene!). For all this, attention, thoroughness, knowledge of biblical sources and familiarity with Romanian and European biblical tradition are required. An edition of The Hieroglyphic History which envelopes historical, philological, but also theological and, last but not least, philosophical notes and commentaries is expected in the future. Article history: Received 3.11.2021; Revised 10.12.2021; Accepted 28.12.2021; Available online 13.04.2022. Rezumat: Corectarea unor erori în ediţiile ştiinţifice ale Istoriei ieroglifice (1705) de Dimitrie Cantemir. Ediţia Panaitescu-Verdeş (1965). Istoria ieroglifică, lucrare scrisă de Dimitrie Cantemir în anul 1705, este considerată primul roman (istoric) românesc. Dincolo de haina alegoriei, a toposului exotic şi a fantasticului animalier, prin decriptări specifice, se revelează evenimente istorice din perioada 1685-1705, care pot constitui pentru un istoric date valoroase. Lucrarea, publicată în 1883 apoi în 1927 şi 1957 în câteva ediţii neştiinţifice, în sfârşit a fost republicată în 1965 într-o ediţie ştiinţifică elaborată de P.P. Panaitescu şi Ion Verdeş. Această ediţie din 1965 are o mare valoare istorică, dar şi câteva lacune, în special în domeniul teologic. Editorii nu indică anumite citate biblice, fac aluzii la idei psihologice pentru citate care sunt clar extrase din Biblie, ignoră filonul biblic care a stat la baza maximelor lui Cantemir, omit să studieze unele toponime la originea lor biblică (Eufrat, Tharsis, Babilon etc.) şi nu realizează că unele idei cantemiriene sunt de origine biblică (de exemplu: evoluţia ciclică a lucrurilor, liberul arbitru). Totodată nu disting unele elemente de iconografie creştină de corespondentele lor biblice, ajungând la confuzii (năframa sfintei Veronica este atribuită de editori Magdalenei!). Pentru toate acestea se cere atenţie, minuţiozitate, cunoaşterea surselor biblice şi familiarizarea cu tradiţia biblică românească şi europeană. O ediţie a Istoriei ieroglifice care să înglobeze notele şi comentariile istorice, filologice, dar şi teologice şi nu în ultimul rând filozofice, este de aşteptat pe viitor. Cuvinte cheie: Dimitrie Cantemir, Istoria ieroglifică, Panaitescu, Verdeş, teologie, evoluţie ciclică, Menandru, Apostolul Pavel, năframa sfintei Veronica